THE NORM OF NON-USAGE AND DETERRENCE OF NUCLEAR WEAPONS: INTERACTION OF THE CONCEPTIONS IN CASE OF THE UNITED STATES - Bladaitė, Neringa (Politologija, 2017)
This article aims to take a closer look to the US nuclear weapons posture during the period of 2009–2015. The cornerstone of the analysis is an existing paradox – although the US is thought to be the country that maintains the norm of non-usage of nuclear weapons, in practice, the US forms the strategy based on nuclear deterrence. In order to implement the main aim of this article, theories of the norm of nuclear weapon non-usage and deterrence were taken into consideration. There are two main parts of this article. Theories that were chosen for the analysis are discussed at the first part of the article. The second part is aimed to find out how the norm of non-usage and nuclear deterrence interacts in practice. The case of the US is analyzed in terms of qualitative content analysis. The statements and remarks of high-ranking US politicians and military officers, official documents and treaties were the main empirical data of the analysis. An analysis of the theories delivered the conclusion that despite certain principal differences, the theoretical combinations of the norm of non-usage and nuclear deterrence are still possible because of the same aim. Both seek the nuclear weapon not be used again. Moreover, the use of both approaches in the same case study helps to get a broader look and see some specifics at the same time. The empirical analysis has shown that the meaning of nuclear deterrence was reconsidered in case of the US. One of the main reasons of reconsideration was the new nuclear doctrine (“Nuclear posture review”), delivered by B. Obama in 2010. According to the new doctrine, the US have to promote disarmament and maintain effective nuclear deterrence at the same time. The psychological elements of this strategy were emphasized in the narrative of new deterrence creation, meanwhile the material ones being relegated to the background. In addition, the form of the nuclear weapon non-usage was transformed into a tradition of non-usage because of the process of dynamics. The tradition of non-usage leaves a small chance of a nuclear weapon usage possibility, which is the necessary condition for the deterrence. From a theoretical point of view, it solves the paradox of norms and deterrence. However, the combination of these concepts seems to be unnatural in practice and it has a negative effect on the implementation of credible deterrence. The not clearly defined nuclear posture of the US may cost the bringing of certain tensions in the future. It can encourage enemies to proliferate a nuclear arsenal or even use it.